Effect of Photobiomodulation with 980nm Diode Laser and Vitamin D on Proliferation and Osteoblastic Differentiation of Periodontal Ligament Stem Cells - Moussavi Jahanabadi, Seyed Amir Hossein; Taleghani, Ferial; Tehranchi, Maryam; Hakimiha, Neda; Hodjat, Mahshid; Saberi Haghighi, Raman (Galen Medical Journal, 2024)
Background: It has been established that periodontal ligament stem cells (PDLSCs) have a significant impact on restoration of periodontal tissues, and optimizing their differentiation into osteoblast is critical to improving clinical outcomes in periodontal regeneration. Different non-invasive method, including photobiomodulation (PBM) and vitamin D supplementation, hold potential for enhancing Osteoblastic Differentiation. the present work aimed at investigating the synergic impact of PBM by the use of a 980 nm diode laser and vitamin D on the osteogenic differentiation and cell viability of PDLSCs. Materials and Methods: Cultured PDLSCs were separated into six groups: 1. Control (no treatment), 2. Vitamin D, 3. PBM at 2 J/cm², 4. PBM at 2 J/cm² with Vitamin D (VD- 2 J/cm²), 5. PBM at 4 J/cm², and 6. PBM at 4 J/cm² with Vitamin D (VD- 4 J/cm²). We evaluated cell viability using the methyl thiazolyl tetrazolium assay at 24 and 72 hours post-irradiation. For the osteogenic differentiation assessment, we measured expression of osteogenic genes, including Runt-related transcription factor 2(RUNX2), Osteocalcin (OCN), alkaline phosphatase (ALP), and Osteopontin(OPN), through quantitative reverse transcription-polymerase chain reaction. Additionally, Alizarin red staining was utilized for detecting calcification. Results: All study groups demonstrated enhanced viability in comparison with the control at both time intervals, with the exception of the vitamin D group at 72 hours. The PBM (4 J/cm²) and VD-2 J/cm² groups exhibited the highest levels of cell viability, respectively. All study groups exhibited increased expression of osteogenic genes in comparison with control group. The largest values were associated with groups that included both vitamin D and PBM. The calcification rate was markedly elevated in the VD-2 J/cm², VD-4 J/cm², and VD+OM groups, respectively. Conclusion: The integration of photobiomodulation with vitamin D has been shown to improve mineralization and accelerate the osteogenic differentiation of PDLSCs, resulting in a synergistic effect.